2005
DOI: 10.17660/actahortic.2005.691.59
|View full text |Cite
|
Sign up to set email alerts
|

The Solar Greenhouse: State of the Art in Energy Saving and Sustainable Energy Supply

Abstract: The objective of the solar greenhouse project was the development of a Dutch greenhouse system for high value crop production without the use of fossil fuels. The project was completed and the results are reported here. The main approach was to first design a greenhouse system requiring much less energy, next to balance the availability of natural energy with the system's energy demand, and finally to design control algorithms for dynamic system control. This paper discusses the first two design steps. Increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(31 citation statements)
references
References 0 publications
1
28
0
Order By: Relevance
“…The momentary energy saving might be 45% and year round 20-25% when compared to single glass (Sonneveld and Swinkels, 2005b), but practical application is still limited due to additional costs for the greenhouse construction and the overall economic benefit. Promising alternatives for the future are double side coated Anti Reflex glass (Hemming et al, 2006a), combinations of micro V treated glass (Sonneveld and Swinkels, 2005a) or triple layer systems (Bot et al, 2005). An extensive simulation study showed that double Anti Reflex glass combines a high diffuse light transmission (82-86%) with an energy reduction of 26%, leading to a gain in energy efficiency of 40%.…”
Section: Minimize Energy Loss By Screens and Insulating Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…The momentary energy saving might be 45% and year round 20-25% when compared to single glass (Sonneveld and Swinkels, 2005b), but practical application is still limited due to additional costs for the greenhouse construction and the overall economic benefit. Promising alternatives for the future are double side coated Anti Reflex glass (Hemming et al, 2006a), combinations of micro V treated glass (Sonneveld and Swinkels, 2005a) or triple layer systems (Bot et al, 2005). An extensive simulation study showed that double Anti Reflex glass combines a high diffuse light transmission (82-86%) with an energy reduction of 26%, leading to a gain in energy efficiency of 40%.…”
Section: Minimize Energy Loss By Screens and Insulating Materialsmentioning
confidence: 99%
“…Examples North West Europe. The solar greenhouse concept as developed by Bot et al (2005) is a perfect example of an integral energy efficient design where all components, including the energy conversion technologies and optimal control are incorporated. The objective of the solar greenhouse project was the development of a greenhouse system for high value crop production without the use of fossil fuels.…”
Section: Integral Design Of Energy Efficient Greenhouse Systemsmentioning
confidence: 99%
“…The Solar Greenhouse project utilized a deep aquifer for seasonal storage to provide complete summer cooling and winter heating for a closed greenhouse (Bot et al, 2005). This system utilized heat pumps and heat exchangers to move energy into and out from storage.…”
Section: Energy Related Issuesmentioning
confidence: 99%
“…With the availability of combined models, the possibilities for designing an overall optimized greenhouse system including covering material, heating and ventilation/dehumidification, control algorithms and energy conversion systems are within sight. The solar greenhouse concept as developed by Bot et al (2005) is a perfect example of model based integral energy efficient design since also the energy conversion technologies and optimal control are incorporated. The objective of the solar greenhouse project was the development of a Dutch greenhouse system for high value crop production without the use of fossil fuels.…”
Section: Integral Design Of Energy Efficient Greenhouse Systemsmentioning
confidence: 99%
“…Using 80% as an average greenhouse light transmission, 80 NGE will enter the greenhouse, qualifying it as a solar collector. The average energy use (in the form of fossil fuel) under the same conditions, is about 40-50 m 3 natural gas per m 2 (Bot et al, 2005). Since the incoming solar radiation represents about twice the energy used in the greenhouse itself, this theoretically creates the possibility to use the greenhouse as a combined crop and heat producing system.…”
Section: Introductionmentioning
confidence: 99%